If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24f + -16fg = 0 Solving 24f + -16fg = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '8f'. 8f(3 + -2g) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'f' equal to zero and attempt to solve: Simplifying f = 0 Solving f = 0 Move all terms containing f to the left, all other terms to the right. Simplifying f = 0Subproblem 2
Set the factor '(3 + -2g)' equal to zero and attempt to solve: Simplifying 3 + -2g = 0 Solving 3 + -2g = 0 Move all terms containing f to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2g = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2g = 0 + -3 -2g = 0 + -3 Combine like terms: 0 + -3 = -3 -2g = -3 Add '2g' to each side of the equation. -2g + 2g = -3 + 2g Combine like terms: -2g + 2g = 0 0 = -3 + 2g Simplifying 0 = -3 + 2g The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
f = {0}
| y/2+5=16 | | 6w+w+8w= | | 14x-190=4x-10 | | 6w-w+6w= | | 2x+65=7x-10 | | 9-7X=9X+21 | | -126-8x=16x+18 | | 5(3x+5)-4(2x-3)=5x+3(2x+12)+1 | | 11x+8=8x-29 | | 59-4x=32x+15 | | -28X-6X=12-10X | | 14-9x=199-44x | | 3+7x=27+1x | | 11X+22=4X+113 | | 2.16x^2-5.40x-3.24=0 | | 60-x=19 | | x-6/10+x-4/15=x+2/6 | | 12*(x-2)+6*(5-x)=4x-6 | | x^4+12x^3+36x^2-64=0 | | 5w^8-45w^7-50w^6=0 | | 3x-4(1-3x)=2x-(x-1) | | 3(x+2)/5=6 | | 4-2(3-2x)=5 | | X+x+x=16 | | 3-5(2x+1)=2x | | 3y^2-9y-84=0 | | 7(2x-1)=-35 | | A(b-2)=c(b+3) | | 6(x+5)=-12 | | 5(x-2)-3(x+1)=0 | | 6x-3=6x+2 | | 100-10x=40 |